(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
Genetic diversity of 40 traditional Bangladeshi rice genotypes was studied under rainfed lowland condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into six clusters. The inter cluster distances were higher than the intra cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster VI contained the highest number of genotypes (12) and the cluster IV contained the lowest (2). The highest intra cluster distance was noticed for the cluster VI and the lowest for cluster IV. The highest inter cluster distance was observed between cluster III and IV followed by clusters IV and V, clusters I and IV, clusters IV and VI and the lowest between clusters II and VI. Regarding inter cluster distance, cluster IV showed high genetic distance from all other four clusters except cluster II. The genotypes from cluster IV could be hybridized with the genotypes of any of the four clusters for producing transgressive segregants. Days to flowering, duration and spikelets/panicle were mainly responsible for genetic divergence while considering mean values. Though filled grains/panicle and flag leaf area are the most positive contributors based on the latent vectors. The highest cluster means for yield and 1000 grain weight and other 2nd highest four yield contributing characters (viz. plant height, days to maturity, panicle length and flag leaf area) were obtained from cluster III. The highest flag leaf area, plant height, panicle length, filled grains per panicle and grain length were found in cluster V. Cluster IV had the lowest mean for yield and other moderate to low yield contributing characters. Therefore more emphasis should be given on cluster V and III for selecting genotypes as parents for crossing with the genotypes of cluster IV which would be used to produce new recombinants with desired traits. DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17048